2007
DOI: 10.1097/01.mlr.0000250863.65686.bc
|View full text |Cite
|
Sign up to set email alerts
|

Did the Medicare Inpatient Rehabilitation Facility Prospective Payment System Result in Changes in Relative Patient Severity and Relative Resource Use?

Abstract: IRF patient composition has not changed meaningfully for Medicare beneficiaries, but patients within payment groups are being provided less care, which could be attributable to the IRF PPS, existing trends in decreasing length of stay, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Our estimates of the effects of the IRF-PPS on costs and outcomes might be biased due to changes in patient characteristics (such as changes in functional status) that are coincident with the implementation of the IRF-PPS but not evident in the claims data that we use for our analysis. However, the likelihood of such bias is small given that we find little or no change in observable characteristics of patients and others studies using richer clinical data and measures of functional status find similar results(Paddock et al 2007). However, it is important to note that we compare average patient characteristics before and after the IRF-PPS.…”
Section: Discussionmentioning
confidence: 50%
“…Our estimates of the effects of the IRF-PPS on costs and outcomes might be biased due to changes in patient characteristics (such as changes in functional status) that are coincident with the implementation of the IRF-PPS but not evident in the claims data that we use for our analysis. However, the likelihood of such bias is small given that we find little or no change in observable characteristics of patients and others studies using richer clinical data and measures of functional status find similar results(Paddock et al 2007). However, it is important to note that we compare average patient characteristics before and after the IRF-PPS.…”
Section: Discussionmentioning
confidence: 50%
“…Selection behavior involves changing admission policies limiting access to less profitable patients (i.e., hip fracture patients with cognitive impairment) while increasing access to patients with more profitable conditions (i.e., hip fracture patients with higher functional independence). 58 Upcoding (ie, deliberately coding higher motor function in patients with hip fracture on discharge), might be an attempt to increase revenue; upcoding is more frequently observed in for-profit facilities and those in more competitive markets. 60,61 Because organizational philosophies and managerial practices in for-profit IRFs (vs. other ownership types [non-profit or government owned IRFs]), reflect differences in decisions that influence service delivery, staffing, patients, and ultimately IRF performance, 56,62 the for-profit IRFs in this study might have been more sensitive to such profit-maximizing strategies and could explain, in part, higher motor function on discharge.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study by Paddock et al 7 looked at changes in a case-mix among patients with stroke, hip fracture, and lower extremity joint replacement. Results suggested that there was no difference in the severity of patients admitted to IRFs pre-versus post-PPS implementation.…”
mentioning
confidence: 99%
“…In addition, even without a change in the case-mix, IRFs in most studies have demonstrated a decrease in length of stay. 710 However, rather than lead to a decreased need for services, Zorowitz 11 notes that the focus on length of stay has increased discharges to skilled nursing facilities (SNFs) prior to the completion of rehabilitation, as well as increased the number of transfers between facilities during care.…”
mentioning
confidence: 99%
See 1 more Smart Citation